PENGEMBANGAN MEDIA PEMBELAJARAN POWERPOINT INTERAKTIF DALAM PEMBELAJARAN IPAS KELAS IV “PERUBAHAN WUJUD ZAT” DI SDN TAMBAKROMO 03 KABUPATEN PATI - Rachma Dinda Lestari; Choirul Huda; Riris Setyo Sundari (STKIP Subang, 2023)
Elementary School Teacher Education Study Program, Faculty of Education, PGRI University Semarang. 2023. The background of making this thesis is due to a problem, namely the not yet developed technology-based learning media in the form of Interactive Powerpoint which is applied in learning. This is influenced by the lack of teachers utilizing technology that is already available in the Interactive Microsoft Office Powerpoint to be used as learning media. Teachers prefer to use the lecture method only and rarely use learning media. The researcher focused his research on one class IV science material, namely